Modified plant‐derived exosomes: Precision medicine in cancer treatment - Swastika Maitra; Subham Sarkar; Bikram Dhara (Wiley, 2024)
Abstract Plant‐derived exosomes (PDEs) are extracellular vesicles (EVs) occurring naturally,which have propitious applications in the development of cost‐effective and fruitful cancer therapy with minimum aftereffects and ramifications. Recent advancements in research based on PDEs demonstrate their extraordinary advantages in cancer therapy. The components of PDEs exhibit accomplished cancer prevention activity and having insignificant or negligible toxicity. The conventional methods to deliver drugs to the target have various problems, several of which can be solved by using PDEs for drug delivery. The main constituents of PDEs are proteins, lipids, DNA and RNA. PDEs are believed to revolutionize cancer therapy due to their magnificent attributes, but only a few clinical trials on PDEs are in progress. The mechanisms and regulations by which PDEs execute anticancer properties are yet not completely understood. Hence, research are conducted worldwide to understand the mechanisms of action of cancer antagonist PDEs more comprehensively and perspicuously. Modified PDEs have prospect in evolution of precision medicine which can bring a new dimension in the treatment of cancer.